Psychosocial factors, acculturation and mental health in Albanian and Bulgarian economic immigrants in Greece - Σπανέα Ευφροσύνη; Καλαντζή-Αζίζι Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF